Synthesis of Phenyl-2,2′-bichalcophenes and Their Aza-Analogues by Catalytic Oxidative Deacetylation - Jiang, Xia; Jin, Hui; Wang, Tingshu; Yoo, Hyebin; Koo, Sangho (Synthesis, 2019)
Efficient synthetic method for medicinally and opto-electronically important bichalcophenes is reported, which highlights Mn(OAc)3/CoCl2-catalyzed oxidative deacetylation of 1,5-dicarbonyl compounds that were easily prepared by conjugate addition of ethyl acetoacetate to α,β-unsaturated carbonyl compounds containing a chalcophene unit. Paal–Knorr reaction of the resulting 1,4-dicarbonyl compounds produced 4-phenyl-2,2′-bichalcophenes and their aza-analogues.
Keywords: bichalcophene; catalytic oxidation; deacetylation; 1,4-dicarbonyl compound; Paal–Knorr reaction